The MI-SDN System to Manage MQTT Data in an Interoperable IoT Wireless Network - et. al., Rajae Tamri, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The main challenge for the Internet of Things (IoT) is to ensure interoperability between heterogeneous IoT entities. To support the interaction, intercommunication, and interoperability between these devices several solutions are proposed in the literature. The SDN (Software-defined Network) is one of these solutions to resolve the problem of the heterogeneous network used in IoT. To guarantee network interoperability, the SDN uses a centralized controller, which handles the entire network. The role of end devices in IoT is only forwarding data. The MQTT (Message Queuing Telemetry Transport) protocol is another solution for granting interoperability in IoT. Which is a publish/subscribe based messaging protocol that avoids direct connection between devices by relaying data through a central server called the broker. Combination of these two solutions to manage IoT devices makes it easy to add new devices without touching or changing the existing infrastructure. The new devices only need to communicate with the broker. Moreover, the Controller SDN is responsible for handling networks. Consequently, smart devices added don’t need to be compatible with the others. In this paper, we present the design and the implementation of a new IoT architecture, which is a combination of SDN technology and MQTT protocol. That enables heterogeneous IoT devices to be interoperable and interact without any problems. Our system utilizes the lightweight protocol MQTT with a new mechanism using several slave brokers and one master. The slaves manage the group of the end devices in the wireless IoT network, and the master broker installed in the SDN controller supervises the integral network. The SDN controller uses a multicast system to send MQTTdata across the external wireless network. As a result, that reduces transmission delay between wireless IoT network compared with the using of a standard MQTT.